TRENDS IN HIGHER EDUCATION IN RUSSIA IN TERMS OF ITS MODERNIZATION - Elena V. Nikitenko (Высшее образование в России)
The article is devoted to the identification and analysis of trends in the development of higher education in Russia in terms of its modernization. The article shows that the core of higher education today is its focus on the needs of the market. In connection with the development of globalization, the need to improve the competitiveness of the national economy primarily through innovative products, higher school faces a new challenge for preparation of a professional, capable for independent search for knowledge, to innovate and create new quality products. Modernization of higher education in Russia requires consistency in systemic reforms, as well as substantial state support.